EFFECTS OF FISCAL REDISTRIBUTION ON GENDER DEVELOPMENT IN INDONESIA: AN ANALYSIS OF THE CHARACTERISTICS OF FISCAL ACCEPTANCE - Hardinandar, Fajrin; Muhammad Firmansyah; Rizky Amelia (Bina Ekonomi, 2024)
Indonesia is still ranked 104th in the world in terms of gender development and is below other ASEAN countries namely Singapore, Malaysia, Viet Nam, and the Philippines. The purpose of this study is to analyze how fiscal redistribution influences gender development through different characteristics in each fiscal revenue with the GMM method. The results show that Gross Regional Domestic Product is influenced by Locally-Generated Revenue, General Allocation Fund, and Tax Sharing. While Specific Allocation Fund and Natural Resources Revenue Sharing worsen Gross Regional Domestic Product. But in the long run, all the effects that worsen Gross Regional Domestic Product are corrected and have an impact on increasing Gross Regional Domestic Product in Indonesia. Then Gender Development Index is influenced by Gross Regional Domestic Product, Locally-Generated Revenue, and General Allocation Fund, while the role of Specific Allocation Fund and Tax Sharing worsens Gender Development Index but in the long run, will increase and increase Gender Development Index. The different types of fiscal revenues also influence the Gender Development Index response as a consequence of the unique characteristics of each fiscal revenue variable. Our suggestion is that local tax sources paid to the center allocated through the balance fund need to consider gender aspects.